2018
DOI: 10.1063/1.5018833
|View full text |Cite
|
Sign up to set email alerts
|

Target scattering characteristics for OAM-based radar

Abstract: The target scattering characteristics are crucial for radar systems. However, there is very little study conducted for the recently developed orbital angular momentum (OAM) based radar system. To illustrate the role of OAM-based radar cross section (ORCS), conventional radar equation is modified by taking characteristics of the OAM waves into account. Subsequently, the ORCS is defined in analogy to classical radar cross section (RCS). The unique features of the incident OAM-carrying field are analyzed. The sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…A circular antenna array is commonly used to generate the vortex electromagnetic waves with different modes, while a single receiving antenna located at the position near the circular array is used to receive the scattering field from the target for OAM-based radar system [22] (shown as Figure 1). To study this problem, we apply the plane wave decomposition method to the transmitted OAM wave and the superposition method to the scattered wave to reconstruct the received signal.…”
Section: Methodsmentioning
confidence: 99%
“…A circular antenna array is commonly used to generate the vortex electromagnetic waves with different modes, while a single receiving antenna located at the position near the circular array is used to receive the scattering field from the target for OAM-based radar system [22] (shown as Figure 1). To study this problem, we apply the plane wave decomposition method to the transmitted OAM wave and the superposition method to the scattered wave to reconstruct the received signal.…”
Section: Methodsmentioning
confidence: 99%
“…where c is the speed of light [29]. As noted, due to the practical focus of the article, there is no need to discuss too much the theoretical part of the electric and magnetic field of the OAM waves.…”
Section: Design Of Uniform Circular Array (Uca)mentioning
confidence: 99%
“…It was concluded that the resolution performance of the OAM‐based imaging radar with infinite OAM modes was equivalent to that of conventional imaging radar [13]. Although the resolution performance cannot be improved by the OAM‐based imaging radar, many simulations have demonstrated that the radar cross sections (RCSs) are different for different incident OAM waves [14, 15]. In addition, experiments were also completed to confirm that the RCSs of complex target were different for different OAM modes [16].…”
Section: Introductionmentioning
confidence: 99%
“…The second one is to make RCS hardly reduce, such as lower carrier frequency and the polarisation radar [20, 21]. Both simulations and experiments have verified the fact that different RCSs can be acquired by emitting different OAM waves, which is similar to the polarisation radar [14–16]. Radio waves with only two kinds of polarisations are radiated in the polarisation radar system, while OAM waves with lots of different modes can be utilised in the OAM radar system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation